Understanding contemporary family support: Reflections on theoretical and conceptual frameworks. - Herrera-Pastor, David; Frost, Nick; Devaney, Carmel (Whiting and Birch, 2020)
Family Support is a transdisciplinary field made up of practices and knowledge from different areas, theories and approaches. This article strives to contribute to the development of this complex epistemological foundation by undertaking a review of the main theoretical frameworks. The relationship between the practice and theory of Family Support is analysed in the paper. A review of the ‘state of the art’ is undertaken, exploring both the role of wide-ranging social theory, and more specific psycho-social theories. Practical examples are provided to ground the analysis. Finally, the article proposes an integrated model proposed providing a critical and versatile approach to understanding different realities. Cross-national joint construction is encouraged to advance Family Support as both a theory and to provide a framework which guides both practice and policy.
Whiting & Birch consent to the deposit of the final paper in University of Malaga's repository.
Keywords: Familias - Trabajo social; Política familiar; Family Support; Epistemological foundation; Research; Practice; Policy; Integrated model